When I Am Asked: Lisel Mueller’s Beginning in Poetry - Justin C. Cordova; James B. Young (Methodist DeBakey Cardiovascular Journal)
Why does anyone write poetry? Lisel Mueller (1924–2020) was a poet, author, and translator with a long and much-decorated career. She and her family fled Nazi Germany in the 1930s and emigrated to the United States, where she would establish herself as a writer. The poem “When I Am Asked” describes the beginning of her journey into poetry, undertaken during a period of grief after the death of her mother. Her writing would come to include nine collections of poetry and myriad accolades, including the 1981 National Book Award and the 1997 Pulitzer Prize for Poetry. Though her ouvre is filled with evocative works, this piece stands out as particularly relevant to physicians and other writers who find solace by expressing themselves through the art of poetry.